Electronic Contract Controls In Islamic Jurisprudence and Law - Abdulsalam Hamood Ghaleb Alanesi (Syura: Journal of Law, 2024)
Electronic contracts are one of the most important developments that the world has witnessed in recent decades, due to the information revolution and modern technologies, as these developments have facilitated the process of contracting between people through the Internet and modern means of communication, and due to the novelty of this type of contracts, Islamic jurisprudence has faced some challenges in its application to its principles and provisions so that it is consistent with contracts in Islamic jurisprudence and its considered controls in their forms and effects, so it was necessary to put these contemporary contracts in the balance of Sharia to be set certain controls Protection of rights This research came to shed light on the concept of electronic contracts and their general controls as well as clarify the controls for conducting these contracts and the researcher used the inductive approach as well as the descriptive approach and the researcher reached a set of results where it is necessary to keep pace with the times, especially in electronic contracts if they have become one of the blessings of the affliction and impose on many also must apply the basics of the contract such as traditional contracts in Islamic jurisprudence as well as must protect rights and clarify the mechanism of conflict resolution In such contracts